1989
DOI: 10.1016/0264-410x(89)90241-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an inactivated oil-adjuvanted rotavirus vaccine in the control of calf diarrhoea in beef herds in Argentina

Abstract: We have assessed the potency of an inactivated oil-adjuvanted rotavirus vaccine in beef herds in Argentina. Two different vaccine trials were conducted. In a small-scale experimental trial, involving 21 pregnant cows (13 vaccinated and eight unvaccinated controls), a significant increase in neutralizing antibody titres against different serotypes of bovine rotaviruses was found in both the colostrum and serum of vaccinated cows compared with that of unvaccinated controls. Seven days after birth, half of the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…Rotaviruses are the major cause of diarrhoea in young calves throughout the world (Bellinzoni et al, 1989;Reynolds et al, 1986;Snodgrass et al, 1986) and of severe acute gastroentreitis in infants and young children . The development of effective vaccines requires an understanding of the major rotaviral antigenic components and their interaction with the host's immune system.…”
Section: Introductionmentioning
confidence: 99%
“…Rotaviruses are the major cause of diarrhoea in young calves throughout the world (Bellinzoni et al, 1989;Reynolds et al, 1986;Snodgrass et al, 1986) and of severe acute gastroentreitis in infants and young children . The development of effective vaccines requires an understanding of the major rotaviral antigenic components and their interaction with the host's immune system.…”
Section: Introductionmentioning
confidence: 99%
“…Serotypes 6 and 10 BRV have both been identified in serotyping studies 1,31 Limited information available on the prevalence of BRV serotypes suggests that serotype 6 is the predominant field strain among isolates from calf diarrhea cases. 31 A third but less common serotype (serotype 8) has been reported among BRV isolates.…”
mentioning
confidence: 99%
“…31 Several other studies have reported BRV strains that are serologitally distinct from serotype 6, but these newly described strains have not been classified relative to other rotavimses. 1,3,4,18,23,32 Although BRV isolates have been detected and serotyped using MAbs, 1,31 there are no reports on the development and use of cDNA probes for the differentiation of BRV serotypes. The objective of this study was to develop and characterize cDNA probes prepared from NCDV, United Kingdom (UK), and Cracker (Cr) VP7 genes for the detection of BRV in cell culture and fecal samples.…”
mentioning
confidence: 99%
See 2 more Smart Citations